Materialistic Considerations in Auditing Financial Statements in BPK RI - Azzahra, Syakirah; Munthe, Emi Dewi Putri; Nst, Dito Aditia Darma (EDUCTUM: Journal Research, 2025)
This study aims to evaluate the application of the materiality concept by auditors at the Indonesian Supreme Audit Agency (BPK RI) in the planning, implementation, and reporting stages of government financial statement audits. Materiality is a threshold used to determine whether misstatements in financial statements can influence the economic decisions of report users. The BPK RI uses standards stipulated in the State Financial Audit Standards (SPKN) and the Technical Instructions for Audits, which adopt international standards (ISSAI). Determining materiality at the BPK generally involves three main components: Planning Materiality, Implementation Materiality (Tolerable Misstatement), and the Posting Threshold. The analysis shows that materiality considerations at the BPK are not only quantitative but also qualitative, given the characteristics of public sector entities that place a strong emphasis on compliance with laws and regulations and public accountability. Misstatements that are small in value but have legal or political impact can be considered material in a BPK audit.